Analysis Of Cost And Gas Emissions In The Distribution Of Gallon Packaged (Case Study At Pt. Xyz) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Transportation is an initial presentation of a supply chain to consumers. Determination of transportation routes greatly affects the costs incurred by companies in distribution activities, an increase in transportation means an increase in the exhaust gas. Motorized vehicles are a source of air pollution in the city of Bandung. Based on these problems, the calculation of transportation costs and exhaust gas emissions is influenced by the distance of delivery on the optimal route. The optimal route is determined by the saving matrix method with asymmetric distances and branch and bound methods with symmetrical and asymmetric distances. This research is to find the most appropriate and optimal shipping route to minimize transportation costs and minimize exhaust emissions. The result of route determination shows that the branch and bound method route has the lowest delivery distance of 38.5 km, while the saving matrix route has a delivery distance of 41.5 km. The most optimal route is generated from the branch and bound method with a transportation cost of Rp. 98,359,445. Exhaust gas emissions of the branch and bound method for each composition of CO, HC, NOx, PM10, CO2, and SO2 are 0.0162 tonnes/year, 0.0035 tonnes/year, 0.0341 tonnes/year, 0.0027 tons/year, 6.1061 tons/year, and 0.0016 tons/year.